Pena, papel e grilhões: o sinuoso caminho até a aprovação da lei do ventre livre - Ana Guerra Ribeiro de Oliveira (2016)
The abolition of slavery in Brazil occurred slowly and gradually, through successive moderate legislation, until the final end of the institution in 1888. In this long journey, the law of free womb represented a change of thought inside the country, because it was edited without the military pressure of the law that gave definitive end to the slave trade. The process, however, was quite slow. Twenty-one years were necessary between the end of (illegal) slave trade and the approval of the next abolitionist law. This postponement can be explained by the tendency of public men of that time to delay any action for emancipation, using, for that, quite ambiguous speeches. On the one hand, almost everyone criticized the institution, contrary to the lights of the Century and the ideal of freedom. On the other hand, it was possible to find several obstacles to the liberation of the slaves. The usual excuses were the lack workers for the farms, the defense of property and the social and economic crisis that any transformation of the slave order could cause. Not only were the political arguments contradictory, but also the views of some important men, such as Perdigao Malheiro, José de Alencar and the Visconde de Rio-Branco, fluctuated over the years. Their judgment weighed to the side of the property or the side of freedom, as sounded the every changing winds of political interests. Because of this political game, the sanction of the free womb law took time and it depended on internal changes that were nececessary to enable the reform. Anyway, after being approved, the law acquired historical significance since it initiated a process of no return, which would ensure the abolition of slave labor, providing a new turn to the side of freedom. As the journey was tortuous and complicated, this study will follow the ways of speeches and political decisions over the years, starting from when the idea of free womb began to gain ground in political battles and going until its approval in 1871. The literature of this time will also be used to help understand the historical period, since the battle for liberty was also reflected in the novels, dramas and poems, especially after the end of slave trade. Just as in political speeches, literary arguments to fight for the emancipation varied and were sometimes even difficult to understand. To defend the end of slavery, the authors used peculiar statements. Some accused the slaves of immoral behavior and, therefore, they would be cancers to be cut off from family life. Others pointed out the sufferings of their existence and the fact that they also deserved equal treatment. Hence, this more direct view of the slave society provided by literary fiction will help compose the picture of nineteenth-century view of the slaves and slavery in Brazil